Urban natural capital accounts: developing a novel approach to quantify air pollution removal by vegetation. Issue 4 (2nd October 2019) - Jones, Laurence; Vieno, Massimo; Fitch, Alice; Carnell, Edward; Steadman, Claudia; Cryle, Philip; Holland, Mike; Nemitz, Eiko; Morton, Dan; Hall, Jane; Mills, Gina; Dickie, Ian; et al.
ABSTRACT: Air pollution presents a major risk to human health, resulting in premature deaths and reduced quality of life. Quantifying the role of vegetation in reducing air pollution concentrations is an important contribution to urban natural capital accounting. However, most current methods to calculate pollution removal are static, and do not represent atmospheric transport of pollutants, or interactions among pollutants and meteorology. An additional challenge is defining urban extent in a way that captures the green and blue infrastructure providing the service in a consistent way. We developed a refined urban morphology layer which incorporates urban green and blue space. We then applied an atmospheric chemistry transport model (EMEP4UK) to calculate pollutant removal by urban natural capital for pollutants including PM2.5, NO2, SO2, O3 . We calculated health benefits directly from the change in pollutant concentrations (i.e. exposure) rather than from tonnes of pollutant removed. Urban natural capital across Britain removes 28, 700 tonnes of PM2.5, NO2, SO2, O3 . The economic value of the health benefits are substantial: £136 million in 2015, resulting from 900 fewer respiratory hospital admissions, 220 fewer cardiovascular hospital admissions, 240 fewer deaths and 3600 fewer Life Years Lost.